2005
DOI: 10.1897/04-368r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dose and particle size on activated carbon treatment to sequester polychlorinated biphenyls and polycyclic aromatic hydrocarbons in marine sediments

Abstract: Recent laboratory studies show that mixing activated carbon with contaminated sediment reduces the chemical and biological availability of hydrophobic organic contaminants. In this study, we test the effects of varying the activated carbon dose and particle size in reducing the aqueous availability of polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs) and the uptake of PCBs by two benthic organisms. We mixed PCB- and PAH-contaminated sediment from Hunters Point Naval Shipyard, San Fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
136
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(154 citation statements)
references
References 17 publications
17
136
1
Order By: Relevance
“…Building on this observation, we have tested in the laboratory a new concept for in-situ sediment management in which activated carbon (AC) is mixed into contaminated sediments to repartition hydrophobic organic compounds and reduce their availability to water and biota. The physicochemical (Zimmerman, Ghosh, Millward, Bridges, & Luthy, 2004;Zimmerman et al, 2005) Francisco Bay, CA, USA, was contacted with 3.4% (dry weight) AC on a roller for one month, we observed 87% reductions in aqueous equilibrium PCB concentrations and up to 84% reductions (McLeod et al, 2007) in the bioaccumulation of PCBs by the clam, Macoma balthica. Six months contact with AC reduced aqueous equilibrium concentrations by over 90% (Zimmerman et al, 2004).…”
Section: Introductionmentioning
confidence: 85%
“…Building on this observation, we have tested in the laboratory a new concept for in-situ sediment management in which activated carbon (AC) is mixed into contaminated sediments to repartition hydrophobic organic compounds and reduce their availability to water and biota. The physicochemical (Zimmerman, Ghosh, Millward, Bridges, & Luthy, 2004;Zimmerman et al, 2005) Francisco Bay, CA, USA, was contacted with 3.4% (dry weight) AC on a roller for one month, we observed 87% reductions in aqueous equilibrium PCB concentrations and up to 84% reductions (McLeod et al, 2007) in the bioaccumulation of PCBs by the clam, Macoma balthica. Six months contact with AC reduced aqueous equilibrium concentrations by over 90% (Zimmerman et al, 2004).…”
Section: Introductionmentioning
confidence: 85%
“…100 sieve to obtain 75-150 ÎŒm-sized particles. Use of smaller-sized particles was shown to improve the performance of AC to sorb HOCs from sediment (Zimmerman et al 2005, Choi et al 2013and 2014. No.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the (bio)availability of various HOCs, including polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and chlorinated pesticides is effectively reduced by AC amendment through laboratory studies as well as pilot-scale demonstrations (Zimmerman et al 2004and 2005, Cho et al 2007and 2009, Tomaszewski et al 2007, Choi et al 2013and 2014. With a smaller impact on benthic ecosystem and sediment bathymetry, it is expected that the treatment technique will serve as an alternative or supplementary option for conventional sediment remediation techniques such as dredging and capping (Ghosh et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the results for columns B2 and B3 reveals that a reduction in biochar particle size lowered the cumulative release of the 16 EPA PAHs by roughly seven orders of magnitude, signifying the importance of biochar particle size in sorption and immobilization of PAHs in soil through providing effective contact between PAH compounds and biochar particles. Reducing activated carbon particle size increased its effectiveness in sorption of PCBs in a PCBcontaminated sediment [47]. Brandli et al (2008) [48] reported that the application of 2% activated carbon in granular and powder forms can reduce PAH concentrations in water phase by 3-64% and 63-99%, respectively.…”
Section: Effect Of Biochar Particle Sizementioning
confidence: 99%